A Porous Perchlorate-Doped Polypyrrole Nanocoating on Nickel Nanotube Arrays for Stable Wide-Potential-Window Supercapacitors - Chen, Gao-Feng (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.